Juvenile Vogt-Koyanagi-Harada Disease in Which Good Visual Prognosis Was Derived from Swift and Definitive Diagnosis - Atsushi Yoshida; Satoko Tominaga; Hidetoshi Kawashima (Case Reports in Ophthalmological Medicine)
We report an 8-year-old girl who manifested Vogt-Koyanagi-Harada (VKH) disease. At the first visit, conjunctival hyperemia, inflammation in the anterior chamber, serous retinal detachment, and papillitis were observed in both eyes. Fluorescein angiography (FA) revealed bilateral subretinal fluid and papillitis. Ocular computed tomography (OCT) showed subretinal fluid and choroidal hypertrophy underneath macula in both eyes. Cerebrospinal fluid examination indicated aseptic meningitis. Systemic data did not suggest the other systemic diseases. Therefore, she was diagnosed with incomplete VKH disease. After corticosteroid pulse therapy, oral prednisolone was administered for seven months. Eighteen days after the induction of the treatments, inflammation in the anterior chamber and serous retinal detachment of both eyes disappeared completely. For seven months after the induction of the treatments, she had no relapses of any symptoms. Cerebrospinal fluid examination and FA for children are difficult to conduct, since it is difficult to get informed consent of these examinations from their parents. However, those thorough examinations enable us to make a swift and definitive diagnosis of VKH disease, thus assuring good visual prognosis. We have to bear in mind that juvenile VKH disease is very rare, yet when it occurs, ophthalmologic examinations help us diagnose and treat it.